Effectiveness of a multi-modal capacity-building initiative for upgrading biomedical waste management practices at healthcare facilities in Bangladesh: a 21st century challenge for developing countries. (March 2022) - Ara, L.; Billah, W.; Bashar, F.; Mahmud, S.; Amin, A.; Iqbal, R.; Rahman, T.; Alam, N.H.; Sarker, S.A.
Summary: Introduction: Biomedical waste management (BMWM) has attracted attention across the world as improper management can pose a serious threat for healthcare workers (HCWs), the general population and the environment. This study aimed to analyse the effectiveness of a multi-modal intervention (MMI) to upgrade BMWM practices at healthcare facilities across Bangladesh. Methods: This quasi-experimental study, with a pre- and post-test design, was undertaken at nine healthcare facilities (five public, three private and one autonomous) over three phases, and concluded in 2019. The MMI included various strategies including: (i) system change; (ii) education and training; (iii) visual reminders; (iv) monitoring and feedback; and (v) ensuring sustainability at the study hospitals. Data collected from 2726 HCWs and waste handlers through direct observation were analysed using Statistical Package for Social Sciences Version 24. Results: Significant improvements were seen in waste segregation practices using colour-coded bins (from 1% to 79%). The use of personal protective equipment during transportation and final management/disposal increased from 3% to 55%. Compliance with the use of standardized methods for collecting and transporting biomedical waste (BMW) increased substantially from 0% to 78%, while compliance with standardized methods for final management/disposal of BMW improved by 39%. Conclusion: Compliance with BMWM practices is very poor in Bangladesh due to a lack of knowledge, manpower and resources. Nevertheless, this MMI can be used as a tool to significantly improve BMWM practices in healthcare facilities. Initiatives such as this MMI will help the Government of Bangladesh to achieve Sustainable Development Goal 3.3 and universal health coverage by 2030.